Development and validation of TreatHSP-QoL: a patient-reported outcome measure for health-related quality of life in hereditary spastic paraplegia - Malina, Jekaterina; Huessler, Eva-Maria; Jöckel, Karl-Heinz; Boog-Whiteside, Eva; Jeschonneck, Nicole; Schröder, Bernadette; Schüle-Freyer, Rebecca; Kühl, Tobias Hans-Jürgen; Klebe, Stephan (Orphanet journal of rare diseases, 2024)
Hereditary spastic paraplegia (HSP) is a rare neurodegenerative disease that lacks specific and validated patient-centered outcome measures (PCOMs). We aimed to develop and validate a health-related quality of life (HRQoL) questionnaire specific to HSP (“TreatHSP-QoL”) that could be used as a PCOM.